2002
DOI: 10.1101/gr.48902
|View full text |Cite
|
Sign up to set email alerts
|

A Fine Physical Map of the Rice Chromosome 4

Abstract: As part of an international effort to completely sequence the rice genome, we have produced a fine bacterial artificial chromosome (BAC)-based physical map of the Oryza sativa japonica Nipponbare chromosome 4 through an integration of 114 sequenced BAC clones from a taxonomically related subspecies O. sativa indica Guangluai 4 and 182 RFLP and 407 expressed sequence tag (EST) markers with the fingerprinted data of the Nipponbare genome. The map consists of 11 contigs with a total length of 34.5 Mb covering 94%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 24 publications
(29 reference statements)
1
42
1
Order By: Relevance
“…Numerous groups have found recombination frequency to vary substantially across the rice genome Wu et al 2003;Zhao et al 2002). The resolution of our new data also made it possible to map recombination hot and cold spots across the genome in this population.…”
Section: Recombination Frequencymentioning
confidence: 86%
“…Numerous groups have found recombination frequency to vary substantially across the rice genome Wu et al 2003;Zhao et al 2002). The resolution of our new data also made it possible to map recombination hot and cold spots across the genome in this population.…”
Section: Recombination Frequencymentioning
confidence: 86%
“…The peak of both QTLs corresponded to the previously mapped position of the mutant locus, brown pericarp, Rc (Kinoshita, 1998 Figure 1B, i). The genetic/ physical distance in this region averages 1.4 Mb/cM, much above the genome average of 200 to 250 kb/cM, as expected for a pericentromeric region (Zhao et al, 2002;Wu et al, 2003). An investigation of the genotype-phenotype relationship in 285 BC2F2 families demonstrated that all 18 families with red grain contained the O. rufipogon allele at either RM125 or the adjacent marker, RG30, suggesting that the gene underlying rg7.1 lay between these two markers.…”
Section: Rough Mapping Of Qtls and The Rc Mutantmentioning
confidence: 99%
“…Localization of large genomic clones, such as bacterial or yeast artificial chromosomes, on chromosomes by FISH and integration of cytological and genetic maps have been demonstrated in several plants (Zhong et al, 1999;Fransz et al, 2000;Cheng et al, 2001a;Kulikova et al, 2001;Howell et al, 2002;Islam-Faridi et al, 2002;Koumbaris and Bass, 2003). The importance of chromosomal mapping of DNA by FISH to the genome research efforts have been distinctly illustrated by the molecular and cytological characterization of a heterochromatic knob on the short arm of Arabidopsis thaliana chromosome 4 (Fransz et al, 2000) and the confirmation of anchored BAC contigs and gene orders in rice (Oryza sativa) (Zhao et al, 2002). In maize, however, the use of BAC clones as FISH probes has been very difficult because maize BAC clones contain large amounts of repetitive elements and their use as FISH probes results in a cross-hybridization throughout the genome.…”
Section: Introductionmentioning
confidence: 99%